Conservation agriculture as a means to mitigate and adapt to climate change, a case study from Mexico - Verhulst, Nele; Govaerts, Bram; Sayre, K.D.; Sonder, Kai; Romero Perezgrovas, R.; Mezzalama, Monica; Dendooven, Luc (Earthscan, 2012)
Conservation agriculture (CA) has been proposed as an adapted set of management principles that assures a more sustainable agricultural production. It combines the following basic principles: (1) reduction in tillage, (2) retention of adequate levels of crop residues and soil surface cover, (3) use of crop rotations. These CA principles are applicable to a wide range of crop production systems. However, the application of CA will be different in different situations. Specific and compatible management components (pest and weed control tactics, nutrient management strategies, rotation crops, appropriately-scaled implements, etc.) will need to be identified through adaptive research with active farmer involvement. In this chapter, climate change predictions for Mexico will be discussed. Then the potential of CA as a means to mitigate and adapt to climate change will be examined for two contrasting agro-ecological environments, using research results of long-term trials. Finally, the economic potential of CA for climate change mitigation and adaption will be examined and an extension strategy will be outlined.